SNS-032 attenuates liver fibrosis by anti-active hepatic stellate cells via inhibition of cyclin dependent kinase 9 - He, Xiao-Li; Hu, Yong-Hong; Chen, Jia-Mei; Zhang, Ding-Qi; Yang, Hai-Lin; Zhang, Lin-Zhang; Mu, Yong-Ping; Zhang, Hua; Chen, Gao-Feng; Liu, Wei; Liu, Ping (Frontiers in Pharmacology, 2022)
Liver fibrosis is a common pathological process of all chronic liver diseases. Hepatic stellate cells (HSCs) play a central role in the development of liver fibrosis. Cyclin-dependent kinase 9 (CDK9) is a cell cycle kinase that regulates mRNA transcription and elongation. A CDK9 inhibitor SNS-032 has been reported to have good effects in anti-tumor. However, the role of SNS-032 in the development of liver fibrosis is unclear. In this study, SNS-032 was found to alleviate hepatic fibrosis by inhibiting the activation and inducing the apoptosis of active HSCs in carbon tetrachloride-induced model mice. In vitro, SNS-032 inhibited the activation and proliferation of active HSCs and induced the apoptosis of active HSCs by downregulating the expression of CDK9 and its downstream signal transductors, such phosphorylated RNA polymerase II and Bcl-2. CDK9 short hairpin RNA was transfected into active HSCs to further elucidate the mechanism of the above effects. Similar results were observed in active HSCs after CDK9 knockdown. In active HSCs with CDK9 knockdown, the expression levels of CDK9, phosphorylated RNA polymerase II, XIAP, Bcl-2, Mcl-1, and ɑ-SMA significantly decreased, whereas those of cleaved-PARP1 and Bax decreased prominently. These results indicated that SNS-032 is a potential drug and CDK9 might be a new prospective target for the treatment of liver fibrosis.